Study of Awareness of Basic Life Support among General Population in Mumbai: A Cross-Sectional Survey (Global Journal of Management and Business Research, 2020)
Background: Bystander basic life support (BLS) leads to a reduction in mortality for out of hospital cardiac arrests (OHCA). Awareness and training of BLS influence the initiation of life support by a layman in the case of OHCA. The study was conducted to assess the awareness and knowledge of BLS and the receipt of BLS training among the general population in Mumbai, India. Methods: The study is a cross-sectional survey using a structured questionnaire. The questionnaire was shared with participants using Google forms through Social media.
Keywords: basic life support; BLS; BLS awareness; BLS training